Atomic-Scale Investigations of Isothermally Formed Bainite Microstructures in 51crv4 Spring Steel - Castro-Cerda, F (Elsevier Inc., 2019)
Atomic-scale investigation was performed on 51CrV4 steel, isothermally held at different temperatures within the bainitic temperature range. Transmission electron microscopy (TEM) analysis revealed three different morphologies: lower, upper, and inverse bainite. Atom Probe Tomography (APT) analysis of lower bainite revealed cementite particles, which showed no evidence of partitioning of substitutional elements; only carbon partitioned into cementite to the equilibrium value. Carbon in the bainitic ferrite was found to segregate at dislocations and to form Cottrell atmospheres. The concentration of carbon remaining in solution measured by APT was more than expected at the equilibrium. Upper bainite contained cementite as well. Chromium and manganese were found to redistribute at the cementite-austenite interface and the concentration of carbon in the ferritic matrix was found to be lower than the one measured in the case of lower bainite. After isothermal treatments close to the bainite start temperature, another austenite decomposition product was found at locations with high concentration of Mn and Cr, resembling inverse bainite. Site-specific APT analysis of the inverse bainite reveals significant partitioning of manganese and chromium at the carbides and at the ferrite/martensite interfaces, unlike what is found at isothermal transformation products at lower temperatures. © 2019